Tenants' complaint handlings system towards the performance of shopping mall facilities / Aqilah Md Sharif and Hairul Nizam Mansor - Md Sharif, Aqilah; Mansor, Hairul Nizam (2019)
Malaysia has been experience the increasing number of shopping mall which lead towards the focuses on facilities management. Property manager use complaint as a benchmark to enhance their product and quality of service towards the shopping mall facilities. Thus, complaint handling system play an important role to improve and review the performance of an organization. However, the inability of property manager and ineffective quality service delivery to deal with customer complaint give tenant bad perception to the property manager. The purpose of this study is to provide insight of complaint handling system related to the performance of shopping mall facilities. This study uses mixed method which comprises quantitative and qualitative method by distributing questionnaires to the tenants and conducting interview with expertise. Management reacts positively towards the complaint system where they agreed that all the essential component is being implemented while tenants responded the opposite way regarding the quality service performance of the facilities.